Development of ordered metal nanoparticle arrangements on solid supports by combining a green nanoparticle synthetic method and polymer templating for sensing applications. Issue 65 (23rd June 2016) - Blanco-Loimil, M.; Pardo, A.; Villar-Alvarez, E.; Martínez-González, R.; Topete, A.; Barbosa, S.; Taboada, P.; Mosquera, V.
Abstract : One step, simple, robust and "green" methodology to fabricate high-density ordered arrays of uniform gold nanoparticles and gold nanoparticles clusters at room temperature over large areas which are suitable for high-performance SERS. Abstract : In this paper, we present a one step, simple, robust and "green" methodology to fabricate high-density ordered arrays of uniform Au nanoparticles (NPs) and Au NP clusters at room temperature over large areas which are suitable for high-performance surface enhanced Raman spectroscopy (SERS). The method is based on the template-guided self-assembly process undergone by polystyrene- b -poly(4-vinylpyridine) copolymer (PS- b -P4VP), in which gold salt is incorporated within the micellar cores (P4VP) and subsequently reduced by HEPES buffer salt in a reduction process at room temperature to give single and clustered NP arrays with hexagonal order. Sizes of P4VP domains are nearly constant ( ca. 27 nm) and contain clusters of tiny Au NPs of ca. 4 nm separated 2–3 nm each other. Moreover, the clusters can be transformed either on singly dispersed anisotropic ("nanocrescent-like") or spherical NPs only by their exposure to O2 plasma. Excellent SERS performance with high signal intensities (as evidenced by high enhancement factors >8 × 10 5 ) and excellent reproducibility were found for the cluster arrays. This is because of the uniform size and gap distance of the gold clusters in large areas. The anisotropic and isotropic dispersed NP metallic substrates also displayed good sensitivities but with relatively slightly lower enhancement factors ( ca. 10 4 to 10 5 ). All these metallic substrates can be achievable without the use of any expensive equipment or clean room processing enabling the potential obtention of low-cost and high-throughput production of chips for (bio)sensing applications.